Sveinn Pálsson, Draft of a Physical, Geographical, and Historical Description of Icelandic Ice Mountains, on the Basis of a Journey to the Most Prominent of Them in 1792–1794. An Annotated and Illustrated English Translation - Ísleifsson, Sumarliði R. (Journal of Northern Studies, 2008)
Review of: Sveinn Pálsson, Draft of a Physical, Geographical, and Historical Description of Icelandic Ice Mountains, on the Basis of a Journey to the Most Prominent of Them in 1792–1794. An Annotated and Illustrated English Translation, eds. Richard S. Williams & Oddur Sigurðsson, Reykjavík: Hið íslenska bókmenntafélag 2004, ISBN 9979661461, 183 pp.